2022
DOI: 10.7554/elife.74242
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative MRI reveals differences in striatal myelin in children with DLD

Abstract: Developmental language disorder (DLD) is a common neurodevelopmental disorder characterised by receptive or expressive language difficulties or both. While theoretical frameworks and empirical studies support the idea that there may be neural correlates of DLD in frontostriatal loops, findings are inconsistent across studies. Here, we use a novel semiquantitative imaging protocol – multi-parameter mapping (MPM) – to investigate microstructural neural differences in children with DLD. The MPM protocol allows us… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 121 publications
1
11
0
Order By: Relevance
“…The suggestion that children with DLD have impaired implicit learning is supported by behavioral data [ 49 , 64 , 82 ]. Additionally, brain structures linked to implicit learning show abnormalities in individuals with DLD (e.g., [ 55 , 56 ]. Theories such as the Procedural deficit hypothesis propose that because implicit learning is impaired in children with DLD, intervention should capitalize on declarative mechanisms [ 85 ].…”
Section: Introductionmentioning
confidence: 99%
“…The suggestion that children with DLD have impaired implicit learning is supported by behavioral data [ 49 , 64 , 82 ]. Additionally, brain structures linked to implicit learning show abnormalities in individuals with DLD (e.g., [ 55 , 56 ]. Theories such as the Procedural deficit hypothesis propose that because implicit learning is impaired in children with DLD, intervention should capitalize on declarative mechanisms [ 85 ].…”
Section: Introductionmentioning
confidence: 99%
“…One hundred and seventy-five children took part in the Oxford Brain Organisation in Language Development (OxBOLD) project (see Krishnan et al, 2021 , 2022 ). We included participants older than 10 years and younger than 16 who had grown up in the United Kingdom speaking English.…”
Section: Methodsmentioning
confidence: 99%
“…Like other neurodevelopmental disorders, there are overlapping WH abnormalities in developmental language disorder (DLD) and ASD. Specifically, in both conditions, the volume of WM is increased in the frontal and temporal lobes [ 29 ], and in children with DLD, increased WM volume was found in the dorsal striatum [ 30 ]. These findings suggest the presence of abnormal myelinization in both disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, it can be concluded that WM plays a crucial role in learning and information processing, but it is also involved and associated with neurological and psychological disorders. Specifically, WM deficiencies have been linked to a variety of psychiatric disorders, including schizophrenia, chronic depression, bipolar disorder, obsessive–compulsive disorder, and posttraumatic stress disorder, as well as neurodevelopmental disorders such as autism spectrum disorder, attention-deficit hyperactivity disorder, developmental language disorder, and dyslexia [ 11 , 13 , 14 , 15 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%